Improving Students’ Academic Achievement in Biology Subject - Nithlavarnan, A.; Mukunthan, T. (South Eastern University, 2011)
Hindu College is a leading National school in the Jaffna district. There are 2315 students in this school. Students are belong selected to this school on merit. Most of the students passed the Grade-5 examination. Students’ G.C.E (O/L) achievement is also satisfactory. In last two years this school obtained 100% pass in G.C.E (O/L). But the G.C.E (A/L) performance is degreasing in recent years. 65 students did not pass any one of the subjects last year. So, due to the above reason this project has becomes predominant. Twenty two students from a J/Hindu College and their parents participated in this study. There are 61 students studying bio- stream in Grade – 13 (batch of 2012). Out of 61 students only 22 weak students were selected for this study. The objectives of this is are to identify the factors related with students’ low achievement level of biology, to identify and plan the intervention to improve the students’ achievement level, implement the intervention, to evaluate the effectiveness of the intervention continuously and to increase the students’ achievement level through the intervention. Pre-survey for students, post-survey for students, interviews with parents, conducted parentteacher conferences, pre-test in Biology, post-test in Biology, document ( Marks schedule, Attendance Register) are the methods of data collecting in this study. Problems faced by students regarding learning of biology in their home are laziness, duration of learning is less at home, no self-learning at home, often sleepily in class, there is no proper place for study at home, there is no hard work and memorization is difficult, there is no freedom at home, and loss of memory. Conducted extra classes (morning & evening classes) and more practical sessions, organized and arranged local fieldtrip within Jaffna, encouraged Biology related group activities, conducted remedial teaching, enhancing Biology instruction via Multimedia presentations, established “Nature Appreciation Club” (NAC) in school in and encouraged students to be involved Biology related activities through this club, conducted parent-teacher meeting regularly and encouraged students participate in biology seminar, which conducted by Professor. Sarath Gottagama was the methods which used to improve the students’ academic achievement. Post-test marks of the students are higher than the pre-test marks, Regular attendance to the school also increasing the students’ academic achievement, the incorporation of IT into the Biology classroom can be accomplished by approaching variety of avenues, the complexity of the Biology topics introduced can be overcome by connecting the biological principles to the students’ “real-world” experiences, part of the solution to improve biology education is to help ensure that students are taught by teachers with expertise in their subject areas, parents to meet often with their child’s teachers not to disturb but to receive feedback as how your child is doing in science courses and to uplift the child’s performance, parent – teacher Corporation helps to improve the students’ achievement, out of school activities help to improve the students’ academic achievement, such as field trips and educational tours, students acquire more knowledge, attitudes, and skills through practical than lecture method, factors related to students help to improve the student achievement, such as moral character, Proper note taking, practical recording, extra reading, and self-motivation and peer coaching.
Keywords: Biology; Academic achievement